Sistem Informasi Manajemen Pengelolaan Sistem Penyediaan Air Minum Dan Sanitasi Desa Bintoyo Berbasis Web - Tomi Tristono; Candra Budi Susila; Nur Rohmad (LPPM Universitas Merdeka Madiun, 2024)
KPSPAM Panguripan is a paid water well management that belongs to the assets of Bintoyo Village. The task of this management is to manage and operate clean water wells so that customers, namely the people of Bintoyo Village, can feel the benefits. Currently, the management is still having difficulty managing the well because it uses manual methods in carrying out its operations. For example, when creating invoices for customers, they still use the manual method, using Microsoft Word by recording them one by one and adding them with a calculator to determine the amount of the customer's bill. Management requires an advanced system integrated with information technology to save time and facilitate the management of these paid clean water wells. A web-based water supply and sanitation management information system has been successfully built using the Waterfall application development method. The system is declared to be running well. It is proven by the existence of system testing using the black box testing method. This system can help simplify management in managing the Panguripan KPSPAM in Bintoyo village.